2010
DOI: 10.1111/j.1530-0277.2010.01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dissolved Oxygen Concentration on the Pharmacokinetics of Alcohol in Humans

Abstract: In conclusion, elevated dissolved oxygen concentrations in alcoholic drinks accelerate the metabolism and elimination of alcohol. Thus, enhanced dissolved oxygen concentrations in alcohol may have a role to play in reducing alcohol-related side effects and accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The concentration of dissolved oxygen in alcoholic beverages can be increased using a method patented by Sunyang Co. Ltd., Korea. This was clearly stated in our article (Baek et al, 2010), and there is no conceivable conflict of interest between the authors and Sunyang Co. Ltd., Korea.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…The concentration of dissolved oxygen in alcoholic beverages can be increased using a method patented by Sunyang Co. Ltd., Korea. This was clearly stated in our article (Baek et al, 2010), and there is no conceivable conflict of interest between the authors and Sunyang Co. Ltd., Korea.…”
supporting
confidence: 69%
“…Recently, there has been extensive publicity surrounding the suggestion that a high concentration of dissolved oxygen in alcohol may help reduce alcohol-related side effects; however, scientific evidence for this claim is lacking. Therefore, we investigated the effect of dissolved oxygen on the pharmacokinetics of alcohol in healthy volunteers (Baek et al, 2010). We found that elevated dissolved oxygen concentrations in alcoholic drinks shortened the time required for the blood alcohol concentration (BAC) to reach 0.000% or 0.050%, without causing a significant difference in the maximum BAC (C max ) or the time to reach the maximum BAC (T max ) after alcohol ingestion.The publication of our results in Alcoholism: Clinical and Experimental Research has created worldwide interest, and Lachenmeier and Rehm (2010) have provided some valuable comments on the article.…”
mentioning
confidence: 99%
“…A similar physiological effect has also been observed in liver’s metabolism of alcohol in humans. Several studies have recently reported that oxygenated alcohol beverages resulted in increased rates of blood alcohol clearance [27, 28]. Based on the combined evidence from animal, hepatocyte and human alcohol studies, we hypothesize that enhanced lactate clearance following OS ingestion is potentially mediated by increased hepatic metabolism; however this hypothesis can only be tested via in-vivo measurement of liver O 2 concentrations and/or liver enzyme activity.…”
Section: Discussionmentioning
confidence: 98%
“…One major criticism of the paper is the very selective citation of the literature, especially regarding the fact that the research results are in stark contrast to the earlier findings in humans mentioned above (Laakso et al., 1979; Maring and von Wartburg, 1980). We also think that the ingestion of higher volumes of oxygenated beverages (the subjects in both earlier studies drank 200 ml of oxygenated water in 30‐min intervals following the ingestion of alcohol for a total of 2 l) would have been more likely to produce an effect than the current study design of Baek and colleagues (2010), in which only 40‐ml portions of oxygenated alcoholic beverage were ingested (total 360 ml in the highest dose group). However, the effective mechanism may have been restricted to the simultaneous application of oxygen and alcohol.…”
mentioning
confidence: 74%
“…The recent article of Baek and colleagues (2010) has renewed the interest in the oxygenation of alcohol, as it suggested that elevated oxygen concentrations in alcoholic drinks accelerate the metabolism and elimination of alcohol. Not based on actual experimental observation, the article also concluded that the oxygen‐enriched alcoholic beverage might reduce hangover and miserable effects because of acetaldehyde including headache, and might even reduce alcohol‐related accidents.…”
mentioning
confidence: 99%